REHABILITASI PENYALAHGUNAAN NARKOBA MENUJU ZERO PREVALENSI (Studi Pada Badan Narkotika National Provinsi Lampung) - veni revina (Ijtihad, 2022)
Drug addicts “sacrifice themselves” because they suffer toxidrome as a result of their own substance abuse. Article 54 of Law Number 35 of 2009 concerning Narcotics says that victims of narcotics abuse need medical and social rehabilitation. The purpose of this research is to analyze efforts to rehabilitate drug abuse towards Zero Prevalence at the National Narcotics Agency of Lampung Province and the Inhibiting Factors in Efforts to Rehabilitate Drug Abuse Towards Zero Prevalence at the National Narcotics Agency of Lampung Province. The research method used in this thesis research is a normative juridical approach. Efforts to Rehabilitate Drug Abuse Towards Zero Prevalence at the National Narcotics Agency of Lampung Province by strengthening Report Receiving Institutions (IPWL) in various sections, namely; Strengthening HR, Certification of Addiction Counselors, Strengthening Bimtek (Technical Guidance), Monev (monitoring/evaluation). There are 2 inhibiting factors in the implementation of Obligatory Report Receiving Institutions (IPWL), two inhibiting factors, internal inhibiting factors and external inhibiting factors.